Localized surface plasmon resonance based nanocube-nanosphere dimer biosensor - Ahmed, Arik Rafiquddin (BRAC University, 2018)
This Thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Applied Physics and Electronics, 2017.